2020
DOI: 10.35848/1347-4065/abaac4
|View full text |Cite
|
Sign up to set email alerts
|

Multibubble sonoluminescence and bubble dynamics in glycerol/water mixture system

Abstract: We investigated viscosity dependence of sonoluminescence (SL) in aqueous solutions of glycerol at acoustic frequencies of 50 and 150 kHz. The concentration dependence of SL intensity showed opposite behaviors at the two frequencies. At 50 kHz, the SL intensity increased with increasing glycerol content taking a maximum at 80% glycerol. At 150 kHz, the SL intensity decreased monotonically with increasing glycerol content. Highspeed shadowgraphy of cavitating bubbles with a frame speed of 1 Mfps demonstrated the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 33 publications
0
0
0
Order By: Relevance
“…It should be noted that a high liquid viscosity leads to the formation of peculiar bubble structures [32,33] that may also impact jetting. Ban and Choi [34] observed the formation of bubble clusters in Kr-saturated 80% glycerol (ν ≈ 100 mPa s) sonicated at 50 kHz that were similar to the clusters reported to emit Na-atom emissions and exhibited droplet injection in Xe-saturated NaCl-ethylene glycol (ν ≈ 15.5 mPa s) at 28 kHz [35].…”
Section: Time Evolution Of the Sl Spectra Of A Very Dry Il With 5 S A...mentioning
confidence: 65%
See 1 more Smart Citation
“…It should be noted that a high liquid viscosity leads to the formation of peculiar bubble structures [32,33] that may also impact jetting. Ban and Choi [34] observed the formation of bubble clusters in Kr-saturated 80% glycerol (ν ≈ 100 mPa s) sonicated at 50 kHz that were similar to the clusters reported to emit Na-atom emissions and exhibited droplet injection in Xe-saturated NaCl-ethylene glycol (ν ≈ 15.5 mPa s) at 28 kHz [35].…”
Section: Time Evolution Of the Sl Spectra Of A Very Dry Il With 5 S A...mentioning
confidence: 65%
“…It is interesting to compare the [BEPip][NTf 2 ] case to that of glycerol aqueous solutions because of their similar viscosities. Ban and Choi [34] observed that the 50 kHz SL intensity of glycerol solutions saturated with Kr increased from 0 to 80% glycerol, then decreased to pure glycerol, which they attributed to the too strong damping of the bubble oscillations at the high viscosity of pure glycerol (934 mPa.s). It is also at 80% glycerol that bubble clusters were reported, clusters that were correlated to the line emission in SL.…”
Section: Time Evolution Of the Sl Spectra Of A Very Dry Il With 5 S A...mentioning
confidence: 99%